Calculation of TVL and HVL for Shielding Requirements in Radiotherapy Facilities using Monte Carlo Simulation - Dewa Ngurah Yudhi Prasada; Akbar Azzi (Departement of Physics Faculty of Mathematics and Natural Sciences, and Institute of Research and Community Services Udayana University, Kampus Bukit Jimbaran Badung Bali, 2025)
Shielding is a critical aspect of radiation therapy facility design to ensure the safety of both workers and the public. This study utilizes the Particle and Heavy Ion Transport System (PHITS) version 3.35 Monte Carlo code to evaluate the tenth-value layer (TVL) of four common materials, like water (1 g/cm³), concrete (2.35 g/cm³), steel (7.8 g/cm³), and lead (11.36 g/cm³), under various photon beam energies of Ir-192 and Co-60 and with various linac energy of 6 MV, 10 MV, and 15 MV, that representing sources typically used in brachytherapy and external beam radiotherapy. The point source, isotropic source, and collimated source were utilized in this research. Results show that TVL values increase with higher beam energy and decrease with denser materials, following the known principles of radiation attenuation. However, an anomaly was observed in lead, where TVL values decreased at energies ≥10 MV, possibly due to pair production effects, which warrants further investigation. None of the results precisely matched the reference values from IAEA SRS-47, likely due to differences in beam spectrum and inherent filtration. These findings suggest that Monte Carlo simulation is a feasible method for estimating shielding requirements, but validation through measurement is recommended.